Pola Perlukaan Kecelakaan Lalu Lintas Lansia Berdasarkan Data HDSS Sleman Pada Tahun 2020-2022 - Wiraagni, Idha Arfianti; Supriyadi, Shea Sapphira; Artanti, Martiana Suciningtyas Tri; Priyambodo, Dewanto Yusuf (Fakultas Kedokteran, Universitas Palangka Raya, 2025)
Traffic accidents are incidents that have a high incidence and can cause great losses to society. In cases of traffic accidents, it is recorded that many non-productive ages experience serious injuries. This study aims to analyze the pattern of traffic accident injuries in the elderly in Sleman based on Sleman HDSS data for 2020-2022. This study is an analytical observational study with a cross-sectional approach. The population of this study was the people of Sleman Regency aged 60 years and over. The sampling technique used is simple random sampling. Based on the analysis of 272 respondents with 401 cases of injury, it was found that the most injuries occurred in the lower limbs and the degree of injury was mild with the most types of combined injuries. For moderate and severe degrees of injury, they have the same prevalence. Burns are the type of injury with the least, namely only 1 case. The largest number of respondents were elderly people aged 60-70 years, namely 72% of the total respondents. The conclusion of this study is that minor injuries are the most common type of injury, with lower limbs being the most common location of injury and combination injuries being the most common type of injury. In the bivariate results, there was no relationship between age and type, location, and severity. This shows that type, location, and severity can occur at any age and do not differ in each age group.